Multi-Environment Variety Testing (Pre-Met) for Irrigated Ecosystem in Rice (Oryza Sativa L.) - Haque, Md. Maksudul; Anisuzzaman, M; Ahmed, M.M Emam; Biswas, Partha S; Ali, Md. Ansar (International Journal of Sustainable Agricultural Research, 2017)
A set of 100 IRRI bred advanced breeding lines were tested at Gazipur (as moderate productive control site) and at Habiganj (as high productive site) following row-column design with 2 replications. The breeding lines were highly variable in days to maturity and plant height but not in grain yield. However the interaction effects between genotype and environment (GXE) were significant for all three traits. At Gazipur, the breeding lines yielded with range between 3.3 to 7.3 t/ha with a growth duration range of 138-154 days, while at Habiganj they yielded 5.1-7.9 t/ha with growth duration of 139-159 days. The highest yielding genotype was IR99092-B-B-78 followed by IR13A390, IR99061-B-B-7, IR14D111, etc at Gazipur, while IR13A390 followed by IR100008-91-B yielded the highest at Habiganj site. Based on yield and growth duration, 22 breeding lines showing better performance at Gazipur, 9 lines at Habiganj and 2 lines for both locations were selected for further evaluation.